A Comparative Analysis of Adopters and Non‐adopters of Drip Irrigation under Plastic Tunnels for Cucumber (Cucumis sativus L.) Production in Balochistan, Pakistan. (25th January 2022) - Qasim, Said; Qasim, Muhammad; Hassan, Anees; Murtaza, Ghulam; Khan, Amir Nawaz
Abstract: This research tries to compare the water use efficiency, electricity efficiency and economic efficiency of adopters and non‐adopters of drip irrigation under plastic tunnels (DIUPT). Data regarding the socio‐economic conditions of farmers and their views on the advantages and disadvantages of the DIUPT were collected through a questionnaire survey of 200 farmers. For expenses, income, electricity efficiency and water use efficiency, we collected data only from the sample farmers, i.e. one adopter and one non‐adopter. Results also revealed that the total horsepower (HP) hours of water per acre used for drip‐irrigated cucumber under plastic tunnels was 240 compared to 576 HP hours for the flood method of irrigation, thereby saving 58% (336 HP hours) of energy. In other words, with the same amount of water used for irrigating 1 acre of cucumber under flood irrigation, 2.4 acres of cucumber could be irrigated using drip irrigation. Realizing about 51% higher yields under drip irrigation, adopters enjoy 40% higher returns than non‐adopter farmers. The study recommends dissemination of information to farmers about DIUPT through training and seminars. Adoption of these technologies would lead to efficient and sustainable use of already depleting water resources in the drought‐prone province of Balochistan. Résumé: Cette recherche tente de comparer l'efficacité de l'utilisation de l'eau, l'efficacité électrique et l'efficacité économique des adoptants et des non‐adoptants de l'irrigation au goutte à goutte sous des tunnels plastiques (DIUPT). Les données concernant les conditions socio‐économiques des agriculteurs et leurs opinions sur les avantages et les inconvénients de la disparition ont été collectées par le biais d'une enquête par questionnaire auprès de 200 agriculteurs. Pour les dépenses, les revenus, l'efficacité de l'électricité et l'efficacité de l'utilisation de l'eau, nous avons collecté des données uniquement auprès des agriculteurs de l'échantillon, c'est‐à‐dire un adoptant et un non‐adoptant. Les résultats ont également révélé que la puissance totale en chevaux (HP) heures d'eau par acre utilisée pour le concombre irrigué sous tunnel plastique était de 240 comparé à 576 HP heures pour la méthode d'irrigation par inondation, ce qui a permis d'économiser 58% (336 HP heures) d'énergie. En d'autres termes, avec la même quantité d'eau utilisée pour irriguer un acre de concombre sous irrigation par inondation, 2, 4 acres de concombre pourraient être irrigués en utilisant l'irrigation goutte à goutte. Réalisant environ 51% de rendements supérieurs sous irrigation goutte à goutte, les adoptants ont des rendements de 40% supérieurs à ceux des agriculteurs non adoptants. L'étude recommande aux agriculteurs de diffuser des informations sur le DIUPT par le biais de formations et de séminaires. L'adoption de ces technologies permettrait une utilisation efficace et durable des ressources en eau déjà épuisées dans la province du Baloutchistan, sujette à la sécheresse.